CHD1 Contributes to Intestinal Resistance against Infection by P. aeruginosa in Drosophila melanogaster - Sebald, Johanna (Public Library of Science, 2012)

(untitled)
Drosophila SNF2-type ATPase CHD1 catalyzes the assembly and remodeling of nucleosomal arrays in vitro and is involved in H3.3 incorporation in viin vivo during early embryo development. Evidence for a role as transcriptional regulator comes from its colocalization with elongating RNA polymerase II as well as from studies of fly Hsp70 transcription. Here we used microarray analysis to identify target genes of CHD1. We found a fraction of genes that were misregulated in Chd1 mutants to be functionally linked to Drosophila immune and stress response. Infection experiments using different microbial species revealed defects in host defense in Chd1-deficient adults upon oral infection with P. aeruginosa but not upon septic injury, suggesting a so far unrecognized role for CHD1 in intestinal immunity. Further molecular analysis showed that gut-specific transcription of antimicrobial peptide genes was overactivated in the absence of infection in Chd1 mutant flies. Moreover, microbial colonization of the intestine was elevated in Chd1 mutants and oral infection resulted in strong enrichment of bacteria in the body cavity indicating increased microbial passage across intestinal epithelia. However, we did not detect enhanced epithelial damage or alterations of the intestinal stem cell population. Collectively, our data provide evidence that intestinal resistance against infection by P. aeruginosa in Drosophila is linked to maintaining proper balance of gut-microbe interactions and that the chromatin remodeler CHD1 is involved in regulating this aspect.